2017
DOI: 10.3310/hsdr05150
|View full text |Cite
|
Sign up to set email alerts
|

Incentives in Diabetic Eye Assessment by Screening (IDEAS) trial: a three-armed randomised controlled trial of financial incentives

Abstract: Background: The UK national diabetic eye screening (DES) programme invites diabetic patients aged > 12 years annually. Simple and cost-effective methods are needed to increase screening uptake. This trial tests the impact on uptake of two financial incentive schemes, based on behavioural economic principles. Objectives: To test whether or not financial incentives encourage screening attendance. Secondarily to understand if the type of financial incentive scheme used affects screening uptake or attracts patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Although his research direction is forward-looking, it lacks reference value. The Judah G trial tested the impact on the adoption of two financial incentive programs based on principles of behavioral economics [ 2 ]. For the derivatives market, he proposed a new contingent claim for domestic or foreign derivatives markets.…”
Section: Related Workmentioning
confidence: 99%
“…Although his research direction is forward-looking, it lacks reference value. The Judah G trial tested the impact on the adoption of two financial incentive programs based on principles of behavioral economics [ 2 ]. For the derivatives market, he proposed a new contingent claim for domestic or foreign derivatives markets.…”
Section: Related Workmentioning
confidence: 99%
“…Providers and staffers felt that transportation, language issues, cultural beliefs or myths, denial and fear were key barriers to DR screening, whereas patients indicated that financial burden and depression were the most common barriers [90]. Judah et al [94] evaluated the effectiveness of financially incentivizing screening among patients in the NHS Diabetic Eye Screening Programme who had not attended an appointment for at least 2 years. There was no difference in attendance between the fixed incentive and control groups (relative risk, 0.70; 95% CI 0.35-1.39), and incentives reduced attendance compared with invitation letters in patients who were regular non-attenders.…”
Section: Barriers To Screeningmentioning
confidence: 99%
“…There was no difference in attendance between the fixed incentive and control groups (relative risk, 0.70; 95% CI 0.35-1.39), and incentives reduced attendance compared with invitation letters in patients who were regular non-attenders. The authors emphasized that future work should focus on non-financial means of overcoming barriers to screening encountered by patients [94].…”
Section: Barriers To Screeningmentioning
confidence: 99%
“…This study was registered with the International Standard Randomised Controlled Trial Number registry (ISRCTN14896403). The report for the funder (National Institute for Health Research) is available online, 9 and justification of the intervention conditions can be found in the published protocol. 10 …”
Section: Methodsmentioning
confidence: 99%